A Study of Effect of Pressure, Temperature and Steam/Natural Gas Ratio on Reforming Process for Ammonia Production - Ali, MS; Sahangir, SM; Badruddoza, AZM; Haque, MR (Journal of Chemical Engineering, 2010)
Journal of Chemical Engineering Vol.ChE 23 1995-2005